RECURSOS DE TECNOLOGIAS DIGITAIS NA EDUCAÇÃO NA PERSPECTIVA INCLUSIVA PARA ALUNOS COM DEFICIÊNCIA VISUAL - Machado, Eduardo Henrique Souza (2022)
The study aims to analyze the educational technologies and pedagogical practices used by teachers who work with students with visual impairments during the covid-19 pandemic, at the Federal Institute of Education - IFES, in the municipality of São Mateus/ES, in the period between March 2020 and March 2022, investigating challenges and proposing alternatives. As a theoretical framework, I used the cultural-historical theory developed by Vigotski, which promotes studies on the individual's psychic development based on social relations, the establishment of signs and the teacher's mediation. The methodology chosen to carry out the study was descriptive and exploratory, in which the research subjects were teachers of basic, technical and technological education who develop pedagogical activities with students with visual impairments. To achieve the results, instruments such as a questionnaire, semi- structured interviews recorded in audio form and analysis of school documents were used. As a result, we identified the difficulties reported by teachers in the learning process of students with visual impairments and in the use of the technological tools available and used in the context of the covid-19 pandemic. From the analysis of these results, it was possible to prepare the Educational Product: Extension course on the use of pedagogical tools in the education of students with visual impairments.